Harnessing the layer-by-layer assembly technique to design biomaterials vaccines for immune modulation in translational applications. (14th February 2019) - Tang, Tan; Weng, Tujun; Jia, Hongxing; Luo, Sida; Xu, Ye; Li, Liuhe; Zhang, Peipei
Abstract : Layer-by-layer (LbL)-based biomaterials vaccines are broadly explored to tune the immunity in different diseases for translational purposes. Abstract : The existence of challenging diseases such as cancers, HIV and Zika requires developing new vaccines that can generate tunable and robust immune responses against the diseases. Biomaterials-based techniques have been broadly explored for designing vaccines that can produce controllable and potent immunity. Among the existing biomaterials-based strategies, the layer-by-layer (LbL) assembly technique is remarkably attractive in vaccine design due to its unique features such as programmed and versatile cargo loading, cargo protection, co-delivery, juxtaposing of immune signals, etc . In this work, we reviewed the existing LbL-based vaccine design techniques for translational applications. Specifically, we discussed nanovaccines constructed by coating polyelectrolyte multilayers (PEMs) on nanoparticles, microcapsule vaccines assembled from PEMs, polyplex/complex vaccines condensed from charged materials and microneedle vaccines deposited with PEMs, highlighting the employment of these techniques to promote immunity against diseases ranging from cancers to infectious and autoimmune diseases ( i.e., HIV, influenza, multiple sclerosis, etc. ). Additionally, the review specifically emphasized using LbL-based vaccine technologies for tuning the cellular and molecular pathways, demonstrating the unique advantages presented by these vaccination strategies. These studies showed the versatility and potency of using LbL-based techniques for designing the next generation of biomaterials vaccines for translational purposes.